Working with loss, death and bereavement : a guide for social workers - Weinstein, Jeremy (SAGE Publications, 2008)
'Working With Loss, Death and Bereavement' helps all those currently working in social work or on training programmes confront and navigate issues of loss, developing the skills and value-base necessary for effective practice.